2013
DOI: 10.5171/2013.256196
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Framework of Human Capital Development of SMEs: The Context of an ERP Project

Abstract: ERP systems are increasingly adopted by SMEs. The ERP system is one of the more complex information systems to implement and its failure rate remains high despite the accumulated experiences. Its implementation indeed requires a large amount of knowledge and technical expertise and skills. Therefore, to facilitate access to the knowledge and expertise that have external partners, SMEs implanting ERP weave social relations (i.e. social conduits) with these external partners. Social conduits allow the transfer k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is a way to fulfil the potentials of employees by expanding their capabilities, and this necessarily implies empowerment of people, enabling them to participate actively in their own development. Diop et al (2013) reported that human capital development enhances the skills, knowledge, productivity, creativity, and inventiveness of people through education and training. However, in other to sustain competitiveness in the organisation; human capital becomes an instrument used to increase productivity.…”
Section: Human Capital Developmentmentioning
confidence: 99%
“…It is a way to fulfil the potentials of employees by expanding their capabilities, and this necessarily implies empowerment of people, enabling them to participate actively in their own development. Diop et al (2013) reported that human capital development enhances the skills, knowledge, productivity, creativity, and inventiveness of people through education and training. However, in other to sustain competitiveness in the organisation; human capital becomes an instrument used to increase productivity.…”
Section: Human Capital Developmentmentioning
confidence: 99%
“…Training and development strategies applied by the firm contribute to human capital. The concept of human capital refers to any knowledge or the acquired characteristics of a person which contribute to his or her economic productivity (Diop, Pascot, Mahmoud, & Mbibi, 2013). Consequently, human capital shapes the orientation of the business, which is related to its performance and prediction of further success to the company.…”
Section: Strategic Human Resource Management and Trainingmentioning
confidence: 99%
“…5. Might enterprise resource planning systems implement CAT in ways that promote human, intellectual, and social capital valuation, as well as development (Diop et al 2013)?…”
Section: Future Issuesmentioning
confidence: 99%